2022
DOI: 10.1007/s12144-022-03252-2
|View full text |Cite
|
Sign up to set email alerts
|

It’s all about beliefs: Believing emotions are uncontrollable is linked to symptoms of anxiety and depression through cognitive reappraisal and expressive suppression

Abstract: The aim of this study was to examine the link between personal beliefs about emotion controllability and symptoms of anxiety and depression, with a particular focus on the mediating role of emotion regulation. To date, there has been little research examining the mediating role of cognitive reappraisal or expressive suppression in the link between beliefs about emotion controllability and symptoms of anxiety. Online questionnaires measuring emotion regulation, beliefs about emotion controllability, and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…These classifications are determined based on specific score ranges. In the case of depression, the five levels are categorized as normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (≥28). Similarly, for anxiety, the levels are categorized as normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (≥20).…”
Section: Classified Output Of Depression Anxiety and Stressmentioning
confidence: 99%
“…These classifications are determined based on specific score ranges. In the case of depression, the five levels are categorized as normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (≥28). Similarly, for anxiety, the levels are categorized as normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (≥20).…”
Section: Classified Output Of Depression Anxiety and Stressmentioning
confidence: 99%
“…In addition, future empirical work could clarify potential mediators and moderators in the relationships between emotion perspectives and clinical outcomes. Initial work in this domain has clarified that differences in emotion regulation, such as the use of cognitive reappraisal or expressive suppression, mediated the relationship between emotion perspectives and mental health, including depressive, anxiety, and eating disorder symptoms (Deplancke et al, 2022 ; Vuillier et al, 2021 ). Additionally, work by Schroder and others describe how anxiety mindsets related to clinical symptoms, such as substance use, depression, and non-suicidal self-injury, and buffered the effect of stressful life events on certain symptoms (Schroder et al, 2017 ).…”
Section: Overview Of Papers and Research Themes Included In The Speci...mentioning
confidence: 99%
“…Consistent with the notion, Tamir et al (2007) found that college students with entity emotion beliefs experienced fewer positive emotions and more negative emotions during the initial period of the transition to college. Moreover, prior studies showed that emotion malleability beliefs were related to psychological symptoms such as depression (De Castella et al, 2018; Deplancke et al, 2022), anxiety (De Castella et al, 2013; Kneeland et al, 2016b; Schroder et al, 2019), and fatigue (Sydenham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%